Estimation of genetic parameters in beef cattle from records of performance - Baharin, K.; Beilharz, R. G. (Commonwealth Scientific and Industrial Research Organization for the Australian Agricultural Council, 1975)
An analysis of the growth and calving performance from a crossbreeding program involving four breeds of sires (Angus, Hereford, Friesian and Shorthorn) mated to three breeds of purebred dams (Angus, Hereford and Shorthorn) and three types of crossbred heifers (Angus X Hereford, Friesian X Angus and Friesian X Hereford) during the 1971 and 1972 calving seasons is presented. The performance of the individual breeds of dams and sires were evaluated from the size and growth rate of their progeny at birth, to weaning and post-weaning, as well as from the performance of the dams at calving measured in terms of incidence of difficult calving, percentage of calves dead at birth and twinning rate. Heritability estimates calculated from intra-class correlation of paternal half-sibs were compared from records obtained from purebred calves and from crossbred calves.Crossbred calves were heavier than the purebred calves at birth and grew faster between birth and weaning. After weaning, crossbred heifers grew significantly faster than the purebreds but no significant difference was observed among the steers. There was no significant difference in performance of crossbred calves produced by the purebred and crossbred dams.Calves from the Friesian sires and Friesian cross dams were heavier at birth than calves produced by the other three breeds of beef sires or the beef crossbred dams and they grew faster to weaning. Between weaning and yearling age both the crossbred steers and heifers from the Friesian sires continued to surpass the performance of the beef breeds of sires but there were no significant differences in the performance of three-breed-cross calves of the Friesian cross dams and the Angus X Hereford dams.Heritability estimates of growth rates calculated from data on the performance of the crossbred progeny generally were lower than those calculated from data of the purebred progeny. Higher estimates of heritability were obtained from the data of female progeny than from male progeny for birth weight but the trend was reversed for growth rates between birth to weaning and from weaning to yearling age.